The elastic fiber network of the anulus fibrosus of the normal and scoliotic human intervertebral disc. - Yu, J; Fairbank, J; Roberts, S; Urban, J (2005)
STUDY DESIGN: Immunohistochemical study of elastic fibers in human intervertebral discs (IVD) collected at surgery from patients with scoliosis. OBJECTIVES: To compare the elastic fiber network in scoliotic discs (idiopathic scoliosis or neuromuscular scoliosis) to that of control (normal) discs. To study whether the change in elastic fiber organization could contribute to the progression of spinal deformity. SUMMARY OF BACKGROUND DATA: Elastin and elastic fibers have been identified previously in human IVD but were believed to contribute little to the tissue's mechanical properties. However, a recent immunohistochemical study has revealed an abundant and organized elastic fiber network in bovine IVD, indicating that elastic fibers could play an important mechanical role. This article reports the organization of elastic fibers in human IVD and the changes of elastic fiber organization in scoliosis. METHODS: Intact wedges of IVD were obtained from patients undergoing surgery for scoliosis (aged 12-22 years). Control discs were obtained from a patient (aged 12 years) with a spinal tumor and a trauma patient (aged 17 years). The discs were dissected to give radial slices and were snap frozen. Frozen sections were cut and digested with hyaluronidase to remove glycosaminoglycans. Micrographs of the sections were examined by polarized light to visualize collagen organization. The elastic fiber network was visualized immunohistochemically or by histochemical staining with orcein. RESULTS: A highly organized elastic fiber network, similar to that described in bovine discs, was revealed in the control human discs. In the anulus fibrosus of control discs, dense elastic fibers were located between adjacent lamellae, with fibers also present within individual lamellae. Elastic fibers appeared to be long (>200 microm) and straight in outer anulus, whereas in inner anulus, they nearly ran parallel to each other and at an angle of approximately 60 degrees or 120 degrees to those in adjacent lamellae. However, in scoliotic discs, elastic fibers were sparse, and the collagen and elastic fiber networks were disorganized with loss of lamellar structure. Cell clusters, one of typical degenerative feature, were seen in scoliotic discs but not in age-matched control discs. CONCLUSIONS: Our results reveal an abundant and organized network of elastic fibers in the adolescent (12 and 17-year-olds) human IVD, and suggest that elastic fiber network plays a significant biomechanical role. This network is sparse and disrupted in scoliotic discs, and could be involved in the progression of the spinal deformity.